Biochemistry a short course - Tymoczko, John L. 1948-; Berg, Jeremy M. (Jeremy Mark) 1958-; Stryer, Lubert (W.H. Freeman & Company, a Macmillan Education imprint, 2015)
Derived from the classic text originated by Lubert Stryer and continued by John Tymoczko and Jeremy Berg, Biochemistry: A Short Course focuses on the major topics taught in a one-semester biochemistry course